2023
DOI: 10.18663/tjcl.1278035
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune inflammation index may predict mortality in dialysis patients

Abstract: Amaç: Böbrek yetmezliğinde artmış inflamasyon söz konusudur. Serum ferritini bir akut faz reaktanıdır. Sistemik immün inflamasyon indeksi, kardiyovaskuler hastalıklarda ve kanserlerde prognostic önemi olduğu gösterilen, nötrofil, lenfosit ve trombosit sayılarından hesaplanan yeni bir belirteçtir. Bu çalışma, sistemik immün inflamasyon indeksinin diyaliz hastalarının mortalite riskini belirlemede kullanılabilirliğini ve mortalite ile ferritin düzeyleri arasındaki ilişkiyi belirlemeyi amaçlamaktadır. Gere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…In a study conducted on patients with Ulcerative Colitis, a significant relationship was found between the systemic inflammation index and disease progression. 18 In the study conducted by Ercan et al 19 it was shown that the systemic inflammation index is effective in determining mortality in dialysis patients. The neutrophil/lymphocyte ratio was used to predict the prognosis of acute cholecystitis patients and was found to be compatible with the severity of cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on patients with Ulcerative Colitis, a significant relationship was found between the systemic inflammation index and disease progression. 18 In the study conducted by Ercan et al 19 it was shown that the systemic inflammation index is effective in determining mortality in dialysis patients. The neutrophil/lymphocyte ratio was used to predict the prognosis of acute cholecystitis patients and was found to be compatible with the severity of cholecystitis.…”
Section: Discussionmentioning
confidence: 99%